Journal of Applied Geodesy (De Gruyter, 2007)
This journal is a forum for research articles in the area of application of geodesy to engineering and other natural sciences. It publishes innovative contributions on sensor developments, multi-sensor systems and sensor data fusion focusing on the capture of georeferenced data. The scope covers various other topics related to applied geodesy, such as optical and microwave 3-D measurement techniques and other sensors for geotechnical measurements.